Pengujian Perangkat Lunak Sistem Informasi Inventori pada Usaha Jasa Pengiriman Paket - Rahman Abdillah; Rudi Hermawan; Wawan Hermawansyah; Ibnu Adkha; Heri Arifin (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Software testing is one of the aspects in software design methodology. The author conducted research by taking a case study on the inventory stock information system in a goods delivery service business. The testing technique for this information system uses the black box testing method, with the Equivalence Partitioning technique. From the testing results, the author found irregularities in the database and conducted a more in-depth analysis of the class diagram. The diversity of software types suggests the importance of flexibility and improvisation during software testing, such as determining the appropriate test cases, selecting the appropriate testing methods, and determining the suitable testing environment. Software testing should also consider the effectiveness of resources, project scheduling and deadlines, user/client requests, the availability of testing infrastructure, and other parameters that may be more complex.